Effect of Instant Noodles Seasoning on Liver Enzymes Parameters Using Albino Rats - Arunsi, Ogbonnaya Mba; Nnatuanya, Isaac; Okwareke, Kalu Nwankwo (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
This study was done to check for the potential toxic effect of instant noodles seasoning on liver enzymes parameters- Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline phosphates (ALP) using Albino rats as a model for the study. Twelve adult female albino rats were divided into three groups each and was fed for 28days. The control group (group 1) was fed with standard rat feed and water only, group 2 (low dose) was fed with rat feed and given 5g of seasoning daily, group 3 (high dose) was fed with rat feed and given 10g of seasoning daily. The serum level was analyzed for AST, ALT and ALP using standard biochemical methods. Data analysis was determined statistically using SPSS version 27 windows 10. The result from the study showed that the control group exhibited mean AST levels of 8.750±0.50 U/L, ALT levels of 6.75±0.95 U/L, and ALP levels of 36.65±1.91 U/L. Low Dose group had, AST levels of 9.750±0.95 U/L, ALT levels of 8.75±0.50 U/L, and ALP levels of 39.75±1.79 U/L. High Dose group had, AST levels of 12.00±0.816 U/L, ALT levels of 11.25±0.50 U/L, and ALP levels of 46.16±0.54 U/L shows a dose-dependant increase in AST, ALT and ALP levels in the treated groups, with statistically significant differences compared to the control (p<0.05). These findings suggest that daily/regular consumption of these seasoning, which contains harmful additives such as monosodium glutamate (MSG), tertiary butylhydroquinone (TBHQ), and excess sodium, may lead to liver damage. The study shows the need for greater awareness of dietary risks associated with processed food additives and highly support the use of natural alternatives for safer liver health.